‘Reading the Mind in the Eyes’: an fMRI study of adolescents with autism and their siblings - Holt, R. J. (Psychol Med, 2014)
BACKGROUND: Mentalizing deficits are a hallmark of the autism spectrum condition (ASC) and a potential endophenotype for atypical social cognition in ASC. Differences in performance and neural activation on the ‘Reading the Mind in the Eyes’ task (the Eyes task) have been identified in individuals with ASC in previous studies. METHOD: Performance on the Eyes task along with the associated neural activation was examined in adolescents with ASC (n=50), their unaffected siblings (n=40) and typically developing controls (n=40). Based on prior literature that males and females with ASC display different cognitive and associated neural characteristics, analyses were stratified by sex. Three strategies were applied to test for endophenotypes at the level of neural activation: (1) identifying and locating conjunctions of ASC–control and sibling–control differences; (2) examining whether the sibling group is comparable to the ASC or intermediate between the ASC and control groups; and (3) examining spatial overlaps between ASC–control and sibling–control differences across multiple thresholds. RESULTS: Impaired behavioural performance on the Eyes task was observed in males with ASC compared to controls, but only at trend level in females; and no difference in performance was identified between sibling and same-sex control groups in both sexes. Neural activation showed a substantial endophenotype effect in the female groups but this was only modest in the male groups. CONCLUSIONS: Behavioural impairment on complex emotion recognition associated with mental state attribution is a phenotypic, rather than an endophenotypic, marker of ASC. However, the neural response during the Eyes task is a potential endophenotypic marker for ASC, particularly in females.